Clostridium difficile in England: can we stop washing our hands? - van Kleef, E; Kuijper, E; Bonten, M; Cooper, B (Lancet, 2017)
Dingle and colleagues1 provide compelling evidence that the substantial decline in Clostridium difficile infection in England since 2006 resulted from the disappearance of fluoroquinolone-resistant isolates. However, attribution of this decline to specific control measures rests on a false premise. The authors state that “if decreases in Clostridium difficile infection were driven by improvements in hospital infection control, then transmitted (secondary) cases should decline regardless of susceptibility”.1 In fact, non-specific hospital infection control measures such as hand hygiene, environmental cleaning, and patient isolation will have a disproportionate effect on resistant strains, provided these strains spread preferentially in the hospital setting.